Intracellular mGluR5 Can Mediate Synaptic Plasticity in the Hippocampus - Purgert, Carolyn A. (Society for Neuroscience, 2014)
Metabotropic glutamate receptor 5 (mGluR5) is widely expressed throughout the CNS and participates in regulating neuronal function and synaptic transmission. Recent work in the striatum led to the groundbreaking discovery that intracellular mGluR5 activation drives unique signaling pathways, including upregulation of ERK1/2, Elk-1 (Jong et al., 2009) and Arc (Kumar et al., 2012). To determine whether mGluR5 signals from intracellular membranes of other cell types, such as excitatory pyramidal neurons in the hippocampus, we used dissociated rat CA1 hippocampal cultures and slice preparations to localize and characterize endogenous receptors. As in the striatum, CA1 neurons exhibited an abundance of mGluR5 both on the cell surface and intracellular membranes, including the endoplasmic reticulum and the nucleus where it colocalized with the sodium-dependent excitatory amino acid transporter, EAAT3. Inhibition of EAAT3 or sodium-free buffer conditions prevented accumulations of radiolabeled agonist. Using a pharmacological approach to isolate different pools of mGluR5, both intracellular and cell surface receptors induced oscillatory Ca(2+) responses in dissociated CA1 neurons; however, only intracellular mGluR5 activation triggered sustained high amplitude Ca(2+) rises in dendrites. Consistent with the notion that mGluR5 can signal from intracellular membranes, uncaging glutamate on a CA1 dendrite led to a local Ca(2+) rise, even in the presence of ionotropic and cell surface metabotropic receptor inhibitors. Finally, activation of intracellular mGluR5 alone mediated both electrically induced and chemically induced long-term depression, but not long-term potentiation, in acute hippocampal slices. These data suggest a physiologically relevant and important role for intracellular mGluR5 in hippocampal synaptic plasticity.